Physics, asked by drikithroshan47461, 1 year ago

(8/27)^-2/3 + (125/64)^1/3

Answers

Answered by ihrishi
1

Answer:

( \frac{8}{27} )^{ -  \frac{2}{3} }  +  (\frac{125}{64} )^{\frac{1}{3} } \\  =  ( \frac{27}{8} )^{  \frac{2}{3} }  +  (\frac{125}{64} )^{\frac{1}{3} }  \\  =  \frac{ {3}^{3 \times  \frac{2}{3} }  }{ {2}^{3 \times  \frac{2}{3} } }  +  \frac{ {5}^{3 \times  \frac{1}{3} } }{ {4}^{3 \times  \frac{1}{3} } }  \\  =  \frac{ {3}^{2} }{ {2}^{2} }  +  \frac{5}{4}  \\  =  \frac{9}{4}  +  \frac{5}{4}   \\  =  \frac{9 + 5}{4}  \\  =  \frac{14}{4}  \\  =  \frac{7}{2}

Similar questions